Revitalisasi Sunnah Dalam Pemikiran Dan Dakwah KH. Ali Mustafa Ya'qub - Mudrikatul Arafah; Daud Rasyid; Muhibuddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The revitalization of the Sunnah has become a crucial issue in contemporary da’wah and hadith studies in Indonesia, particularly amid the widespread dissemination of fabricated (maudhu‘) hadiths through digital media that threaten religious authority and Muslim religious practices. This study examines the thought and da’wah of KH. Ali Mustafa Ya‘qub (1952–2016), a prominent Indonesian hadith scholar, in his effort to revitalize the Sunnah as a contextual yet authentic guide for life. Using a qualitative method with a literature study approach and content analysis of his major works, this research aims to address three questions: the concept of Sunnah revitalization according to Ya‘qub, the hadith criticism methodology he employed, and the relevance of his ideas to the challenges of da’wah in the digital era. The findings show that Ya‘qub constructed Sunnah revitalization upon four pillars of hadith scholarship (muṣṭalaḥ, takhrij, fiqh al-ḥadīth, and difā‘ ‘an al-ḥadīth) while integrating both sanad and matn criticism in a balanced manner. Its implementation appears in preaching, education, and digital engagement, making it relevant today